2021
DOI: 10.3390/pharmaceutics13030353
|View full text |Cite
|
Sign up to set email alerts
|

Applicability of an Experimental Grade of Hydroxypropyl Methylcellulose Acetate Succinate as a Carrier for Formation of Solid Dispersion with Indomethacin

Abstract: The transformation of a crystalline drug into an amorphous form is a promising way to enhance the oral bioavailability of poorly water-soluble drugs. Blending of a carrier, such as a hydrophilic polymer, with an amorphous drug is a widely used method to produce a solid dispersion and inhibit crystallization. This study investigates an experimental grade of hydroxypropyl methylcellulose acetate succinate, HPMCAS-MX (MX), as a solid dispersion carrier. Enhancement of thermal stability and reduction of the glass … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 36 publications
1
9
0
Order By: Relevance
“…[9] Converting crystalline drugs into an amorphous state by disseverance of the crystal lattice may prove a vital approach to enhance drug solubility as it is in the higher energy state. [10,11,12] Nowadays, Solid dispersion (SD) emerged as a novel technique for delivery of drugs to overcome the barriers to drug absorption. In this technique, one or more active ingredients dispersed in a hydrophilic carrier/polymer in a solid-state which can be prepared by various methods i.e.…”
Section: Introductionmentioning
confidence: 99%
“…[9] Converting crystalline drugs into an amorphous state by disseverance of the crystal lattice may prove a vital approach to enhance drug solubility as it is in the higher energy state. [10,11,12] Nowadays, Solid dispersion (SD) emerged as a novel technique for delivery of drugs to overcome the barriers to drug absorption. In this technique, one or more active ingredients dispersed in a hydrophilic carrier/polymer in a solid-state which can be prepared by various methods i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Since it has been reported that the deviation in Tgs values obtained experimentally from the theoretical values indicates the presence of intermolecular interactions between the components [ 35 , 49 ], it was considered that AntiY 5 R and NaTC interacted with each other even in the amorphous state. Furthermore, it has also been reported that the increase in Tg and intermolecular interactions with polymers could inhibit the crystallization of drugs and stabilize an amorphous state during storage in several PASD preparations [ 45 , 51 , 52 ]. Therefore, the co-amorphous system of AntiY 5 R with NaTC would be quite stable, and the amorphous state might be maintained even under accelerated conditions at 40 °C.…”
Section: Resultsmentioning
confidence: 99%
“…Indomethacin was purchased from Kongo Chemical Co., Ltd. (Toyama, Japan). A commercial grade of HPMCAS “Shin-Etsu AQOAT® type MG” and an experimental grade “type MX” originally developed were kindly gifted by Shin-Etsu Chemical Co., Ltd. (Tokyo, Japan) [ 19 ]. GIT-0 lipid (20 wt.% phospholipid dissolved into dodecane), Prisma HT buffer (pH 6.5), and acceptor sink buffer (ASB) were purchased from pION Inc. (MA, USA).…”
Section: Methodsmentioning
confidence: 99%
“…Hence, designing and developing a novel solid dispersion carrier with lower T g is desirable. In a previous study, we focused on an experimental grade of HPMCAS originally designed with lower T g than commercial grade [ 19 ]. Physicochemical investigation of its solid dispersion revealed the formation of intermolecular interaction with indomethacin (IMC) inhibited crystallization.…”
Section: Introductionmentioning
confidence: 99%